Reduce, reuse, redeem: Deposit-refund recycling programs in the presence of alternatives - Berck, Peter; Sears, Molly; Taylor, Rebecca L. C.; Trachtman, Carly; Villas-Boas, Sofia B. (Elsevier, 2024)
Understanding how consumers make recycling decisions is crucial in crafting sustainable recycling policies. We estimate consumer preferences and willingness to pay for current beverage container recycling methods, including curbside pick-up services, drop-off at government-subsidized recycling centers, and drop-off at non-subsidized centers. Using a representative online and telephone survey of California households, we estimate a revealed preference discrete choice model that identifies the key attributes explaining consumers’ beverage container disposal decisions, including the ability to receive a deposit refund (paid to consumers only if they recycle at drop-off centers) and the effort associated with bringing recyclable materials to recycling centers. Additionally, we use counterfactual policy analysis to show that increasing the refund amount increases overall household recycling rates. Infra–marginal households who are on the boundary between taking containers to recycling centers and recycling using curbside pick-up, namely white households and households with higher educational attainment, see the largest changes in consumer surplus generated by increasing refund payments. Conversely, we show that eliminating government-subsidized drop-off centers does not significantly alter consumer surplus for any major demographic group, and has little impact on whether a household chooses to recycle.